Tìm gtnn của D= (x-1)^2 + (x+1)^2 +3. E= x^2+y^2-2x-4y. F= x^2 +y^2 -4xy

Tìm gtnn của D= (x-1)^2 + (x+1)^2 +3. E= x^2+y^2-2x-4y. F= x^2 +y^2 -4xy

0 thoughts on “Tìm gtnn của D= (x-1)^2 + (x+1)^2 +3. E= x^2+y^2-2x-4y. F= x^2 +y^2 -4xy”

  1. Giải thích các bước giải:

    Ta có:

    \(\begin{array}{l}
    D = {\left( {x – 1} \right)^2} + {\left( {x + 1} \right)^2} + 3\\
     = \left( {{x^2} – 2x + 1} \right) + \left( {{x^2} + 2x + 1} \right) + 3\\
     = 2{x^2} + 5 \ge 2.0 + 5 = 5,\,\,\,\forall x\\
     \Rightarrow {D_{\min }} = 5 \Leftrightarrow {x^2} = 0 \Leftrightarrow x = 0\\
    E = {x^2} + {y^2} – 2x – 4y\\
     = \left( {{x^2} – 2x + 1} \right) + \left( {{y^2} – 4y + 4} \right) – 5\\
     = {\left( {x – 1} \right)^2} + {\left( {y – 2} \right)^2} – 5\\
     \ge 0 + 0 – 5 =  – 5\\
     \Rightarrow {E_{\min }} =  – 5 \Leftrightarrow \left\{ \begin{array}{l}
    {\left( {x – 1} \right)^2} = 0\\
    {\left( {y – 2} \right)^2} = 0
    \end{array} \right. \Leftrightarrow \left\{ \begin{array}{l}
    x = 1\\
    y = 2
    \end{array} \right.
    \end{array}\)

    Em xem lại đề câu F nhé!

    Reply

Leave a Comment